Bio-inspired design of an auxiliary fishbone-shaped cathode flow field pattern for polymer electrolyte membrane fuel cells. (1st January 2021) - Wang, Yulin; Si, Chao; Qin, Yanzhou; Wang, Xiaodong; Fan, Yuanzhi; Gao, Yuyao
Abstract: A bio-inspired auxiliary fishbone-shaped flow field (AFFF) pattern is proposed and designed at the cathode flow field plate (FFP) of polymer electrolyte membrane (PEM) fuel cells, in order to enhance under-rib mass transport and water removal from gas diffusion layer (GDL). The bio-inspired AFFF pattern is numerically investigated by a three-dimensional multiphase fuel cell model. It is shown that the AFFF pattern significantly improves under-rib mass transport and water removal ability, hence fuel efficiency is improved. In comparison with the conventional parallel flow field (CPFF) pattern, the new pattern exhibits higher uniformity of reactants and saturation distributions, and thereby improving the operation stability of fuel cells. Furthermore, sub-branch channels of various numbers and widths in the AFFF pattern are evaluated with consideration of electrical contact resistance (ECR) between the FFP and GDL. Under-rib mass transport and water removal is improved when increasing the number and width of sub-branch channels. However, the ECR somehow increases as well. Therefore, counterbalance between under-rib mass transfer and ECR should be considered. Finally, the AFFF pattern with an optimized combination between number and width of sub-branch channels is achieved to improve the maximum power density of fuel cells.